Racial capitalism and epistemic injustice: Blindspots in the theory and practice of solidarity economy in Brazil - Ferreira, Priscilla (Geoforum, 2022)
•Racialization undergirds both capitalism and alternative economics frameworks centered on policy-centrism.•Solidary Economy lacks intersectional socio-spatial analysis of majority Black favela economies.•Solidarity Economy in Brazil has privileged policy-centrism over autonomous grassroots-organizing.•The Movement of Solidarity Economy replicates racialized power-knowledge hierarchies.•The sociospatial and economic knowledge of Black subjects enhances SE theory-building and politics. This article performs a socio-spatial analysis of the political discourse, agendas, and organizing spaces of the Solidarity Economy Movement (MSE) in Rio de Janeiro as a lens to examine how racialized power–knowledge dynamics and race-based socio-spatial inequalities can be replicated in the process of institutionalization of social movements’ agendas. It discusses adverse implications stemming from the MSE’s political choice to disproportionately focus on policy-centrism over grassroots organization as its priority strategy. It also analyses the failures of the white leadership of the movement to acknowledge Black economic traditions, Favela economies, and Black solidarity economies as pivotal experiences to understand and challenge racial capitalism. I draw on two years of participatory ethnographic research in Favela City of God and in Solidarity Economy marketplaces and political spaces across Rio de Janeiro. This paper elucidates a gap in the literature on Solidarity Economy in Brazil in terms of theorizing around race. I contend that a colorblind class-first Marxist approach, in tandem with the perversive myth of racial democracy in Brazil, underpin the movement’s conceptual shortcoming in addressing how racialization is co-constitutive of both capitalism and solidarity economies. I show how such neglect has displaced Black women favela dwellers as knowledge producers and weakened the base support of the movement in ways that is debilitating to its organizational capacity. I argue for the epistemic and political contributions that Black communities’ expertise with solidarity economies can make to critical analysis of racial capitalism and solidarity economies as well as to the endeavor of rethinking political economy.